The electric drive control system of corner reflectors of the spacecraft interferometer; MATEC Web of Conferences; Vol. 102 : Space Engineering - Langraf S. V. Sergey Vladimirovich; Bunkov D. S. Dmitry Sergeevich; Odnokopylov I. G. Ivan Georgievich; Galtseva (Gal’tseva) O. V. Olga Valerievna (2017, 2017)
Title screen